On Reliable Identification of Two Independent Markov Chain Distributions - Navaei, Leader (Mathematical Problems of Computer Science, 2021)
In this paper the problem of logarithmically asymptotically optimal (LAO) identification of distributions for two independent simple homogeneous stationary Markov chains with finite number of states is studied. The problem of identification under reliability requirement of distributions for one Markov chain was studied by Haroutunian and Navaei.